2021
DOI: 10.2174/1871530320666201104115016
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Metabolic Interactions of Human Erythrocytes: A Molecular Perspective

Abstract: Background: Apart from their main function as oxygen carriers in vertebrates, erythrocytes are also involved in immune regulation. By circulating throughout the body, the erythrocytes are exposed and interact with tissues that are damaged as a result of a disease. Methods: In this study, we summarize the literature regarding the contribution of erythrocytes to immune regulation and metabolism. Results: Under the circumstances of a disease state, the erythrocytes may lose their antioxidant capacity and rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 88 publications
0
13
0
1
Order By: Relevance
“…Apart from their typical role as oxygen transporters, human erythrocytes retain a considerable immunomodulatory capacity (11,12). Interestingly, erythrocytes constitute important pools of cytokines, chemokines, S1P, LPA and Cholesterol in the blood (13).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their typical role as oxygen transporters, human erythrocytes retain a considerable immunomodulatory capacity (11,12). Interestingly, erythrocytes constitute important pools of cytokines, chemokines, S1P, LPA and Cholesterol in the blood (13).…”
Section: Introductionmentioning
confidence: 99%
“…This event leads to the formation of ceramide 31 , sphingosine, and release of microvesicles 32 . Interestingly, erythrocyte sphingolipid metabolism can result in the formation of sphingosine 1-phosphate (S1P) 9 , a bioactive lipid mediator, implicated in the pathogenesis of NASH 33 . It has previously been shown that erythrocyte membranes of NASH patients, contain decreased levels of sphingomyelin 34 , and that erythrocyte-conditioned media do not contain elevated S1P 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cells are also important players of the reverse cholesterol transport 9 . Since, cholesterol accumulation contributes to the inflammatory process of NASH, we wondered whether erythrocyte membranes of NASH patients contain increased cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Αξίζει να σημειωθεί ότι τα ερυθρά αιμοσφαίρια είναι ένας τύπος κυττάρου του οποίου ο ρόλος στη ρύθμιση της ανοσολογικής λειτουργίας 409 , και τον μεταβολισμό και την διακίνηση λιπιδίων δεν έχει πλήρως εκτιμηθεί 410 . Η δίαιτα με υψηλή περιεκτικότητα σε λιπαρά προκαλεί αύξηση της χοληστερόλης της μεμβράνης ερυθροκυττάρων 411 , ενώ η γήρανση των ερυθροκυττάρων σχετίζεται με τη συσσώρευση οξειδωμένων φωσφολιπιδίων in vivo 412 .…”
Section: επιδραση λιποτοξικοτητας στο ερυθροκυτταροunclassified